2016
DOI: 10.1038/npp.2016.112
|View full text |Cite
|
Sign up to set email alerts
|

Resting State Brain Network Disturbances Related to Hypomania and Depression in Medication-Free Bipolar Disorder

Abstract: Research on resting functional brain networks in bipolar disorder (BP) has been unable to differentiate between disturbances related to mania or depression, which is necessary to understand the mechanisms leading to each state. Past research has also been unable to elucidate the impact of BP-related network disturbances on the organizational properties of the brain (eg, communication efficiency). Thus, the present work sought to isolate network disturbances related to BP, fractionate these into components asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 42 publications
13
54
0
Order By: Relevance
“…Previous research indicated compromised FC especially between the amygdala and prefrontal regions in acutely depressed BD patients (Li et al, 2015;Liu et al, 2015;Spielberg et al, 2016). However, most studies examining euthymic BD individuals did not report any significant effects in amygdala FC, consistent with our results .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous research indicated compromised FC especially between the amygdala and prefrontal regions in acutely depressed BD patients (Li et al, 2015;Liu et al, 2015;Spielberg et al, 2016). However, most studies examining euthymic BD individuals did not report any significant effects in amygdala FC, consistent with our results .…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to our findings, many studies reported aberrations in the amygdala as a key component of the limbic network. Hyperactivation in the amygdala was not only reported in task‐based fMRI studies presenting emotionally arousing pictures (Townsend & Altshuler, ) but also in prior examinations of resting‐state FC: Previous research indicated compromised FC especially between the amygdala and prefrontal regions in acutely depressed BD patients (Li et al, ; Liu et al, ; Spielberg et al, ). However, most studies examining euthymic BD individuals did not report any significant effects in amygdala FC, consistent with our results (Townsend & Altshuler, ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Thus, network analysis of the brain provides a profound perspective into understanding the structural and functional organizations of the brain in health and disease (Bassett and Bullmore 2009, Bullmore and Sporns 2009, Sporns 2010). Increasing numbers of studies indicate alterations in network configuration of the brain with aging (Meunier, Achard et al 2009, Micheloyannis, Vourkas et al 2009, Sala-Llonch, Bartres-Faz et al 2015), and in neurological disorders such as Alzheimer’s disease (He, Chen et al 2008, Supekar, Menon et al 2008, Stam, de Haan et al 2009, Fang, Yan et al 2015), schizophrenia (Bassett, Bullmore et al 2008, Liu, Liang et al 2008, Rubinov, Knock et al 2009), depression (Leistedt, Coumans et al 2009, Ye, Yang et al 2015, Spielberg, Beall et al 2016), and Parkinson’s disease (Gao and Wu 2016, Tessitore, Santangelo et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Although abnormal functional connectivity is proposed to be a main feature in BD, few studies have focused on whether the underlying structural connectivity is altered in BD using state-of-the-art whole-brain network analysis [24][25][26][27][28][29][30] . As such, complementing the existing knowledge of anatomical and functional deficits in PBD with a comprehensive mapping of altered structural connectivity will inform how brain structure-function coupling is affected, and thus allow for an improved assessment of patients' cognition 27 .…”
Section: Introductionmentioning
confidence: 99%